2008
DOI: 10.1208/s12249-008-9091-3
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin in Lyotropic Liquid Crystalline Formulations: Physical, Chemical and Functional Stability

Abstract: Abstract. The purpose of this study was to develop a lyotropic liquid crystalline formulation using the emulsifier vitamin E TPGS and evaluate its behavior after incorporation of a flavonoid, quercetin. The physical (macro and microscopic), chemical (determination of quercetin content by the HPLC method) and functional (determination of quercetin antioxidant activity by DPPH• assay) stability of the lamellar liquid crystalline formulation containing flavonoid was evaluated when stored at 4±2°C; 30±2°C/70± 5% R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…The association of Vitamin E TPGS, IPM and PG-water in the ratio 1:1 and 3:1 has been previously demonstrated (Vicentini et al, 2008). Polarized light microcopy analysis is shown in Figure 3.…”
Section: Preparation and Characterization Of The Liquid Crystal Phasessupporting
confidence: 55%
See 1 more Smart Citation
“…The association of Vitamin E TPGS, IPM and PG-water in the ratio 1:1 and 3:1 has been previously demonstrated (Vicentini et al, 2008). Polarized light microcopy analysis is shown in Figure 3.…”
Section: Preparation and Characterization Of The Liquid Crystal Phasessupporting
confidence: 55%
“…Liquid crystalline phases were prepared as previously described by Vicentini et al (2008). To obtain the systems, mixtures of surfactant (Vitamin E TPGS) and oil (IPM) were prepared in different ratios (3:1, 1:1 and 1:3 (w/w)), which were diluted with a mixture of water and PG following the same ratio.…”
Section: Formulation Preparationmentioning
confidence: 99%
“…[2][3][4] Topically applied antioxidants can directly enrich the natural antioxidant defense system and prevent/reduce oxidative damage to the skin. 7 Phyllanthus urinaria is a herbal plant belonging to the genus Phyllanthus, family Euphorbiaceae. The genus Phyllanthus is widely distributed in tropical and subtropical countries, including Malaysia, Indonesia, China, Southern India, and South America.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that drug loading might influence the microstructure of liquid crystalline systems via interaction with curved bicontinuous lipid bilayer of liquid crystalline phase, by making the microstructure became unstable and thus resulting in a phase transformation. 60 However, the rheological behavior of Tr-loaded LCG revealed that Tr did not affect the microstructure of LCG significantly.…”
Section: Viscosity Measurementsmentioning
confidence: 94%
“…The anisotropic nature of liquid crystalline system was confirmed under PLM where it showed birefringence due to its molecular organization 39 as shown in Figure 3. As there are some parameters such as drug loading and the alteration of the system components proportions could affect the packing parameter of lecithin, thus affecting the prepared liquid crystalline phase, 60,63 whether drug loading and water capacity would affect the microstructure formed or not was investigated. It was observed that the structure features of the liquid crystals of LCG was not influenced by the incorporation of Tr into the system, but it was mainly affected by water content as depicted in Figure 4.…”
Section: Polarizing Light Microscope Evaluationmentioning
confidence: 99%